1985
DOI: 10.1073/pnas.82.4.1160
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the mycoplasma evolutionary tree from 5S rRNA sequence data.

Abstract: The 5S rRNA sequences of eubacteria and mycoplasmas have been analyzed and a phylogenetic tree constructed. We determined the sequences of 5S rRNA from CMstridium innocuum, Acholeplasma laidlawii, Acholeplasma modicum, Anaeroplasma bactoclasticum, Anaeroplasma abactoclasticum, Ureaplasma urealyticum, Mycoplasma mycoides mycoides, Mycoplasma pneumoniae, and Mycoplasma gallisepticum. Analysis of these and published sequences shows that mycoplasmas form a coherent phylogenetic group that, with C. innocuum, arose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 39 publications
4
73
0
2
Order By: Relevance
“…Moreover, the length lisepticum was shown in [7]), of 5 S rRNA hybridizing fragments in Bg/II digest of We conclude that: there are two 23 S-5 S and three M. Gallisepticum DNA is identical to that of 23 S 16 S hybridizing regions in M. Gallisepticum genome.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the length lisepticum was shown in [7]), of 5 S rRNA hybridizing fragments in Bg/II digest of We conclude that: there are two 23 S-5 S and three M. Gallisepticum DNA is identical to that of 23 S 16 S hybridizing regions in M. Gallisepticum genome.…”
Section: Resultsmentioning
confidence: 65%
“…Pilot exDeriments indicated that the hybridization patterns of digested M. Gallisepticum DNA with the orobes described are identical to that obtained utilizing-23 S rRNA or 16 S rRNA E. coli as probes. Oligonucleotide A01 (ACACCTGGTCC-CATTTCCGAACCC) synthesized according to pub1ishe:d sequence of 5 S RNA of M. Gallisepticum [7] was used as a nrobe for 5 S RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Their genomes range in size from 680 to 1,600 kb (36). Previous analyses of 16s rRNA and 5s rRNA sequences have shown that members of the class Mollicutes are phylogenetically related to gram-positive bacteria (30,40,46,48). It has been postulated that the Mollicutes arose by degenerative evolution from clostridium-like ancestors.…”
mentioning
confidence: 99%
“…Woese and his students determined several bacterial 5S rRNA sequences. They showed that the rRNA sequences could be used as phylogenetic markers for bacteria (15). They also showed that evolutionary variation in sequences could be used to determine how the RNAs fold into secondary structure (so-called phylogenetic comparative RNA structure analysis) (16).…”
Section: Lead Up To the Papermentioning
confidence: 99%